Diversity and Utilization of Medicinal Plants by the Dayak Kenyah Tribe in Punan Gong Solok Village, Malinau Regency, North Kalimantan - Rupa, Darius; Karliandi; Zulfadli; Nursia; Ibrahim; Suciyati, Alfi; Ilma, Silfia; Pasulle, Mia; Navia, Zidni Ilman (Program Studi Biologi, Fakultas Teknik, Universitas Samudra, 2025)
Indonesia is rich in biodiversity and traditional knowledge related to the use of medicinal plants. This study aims to document medicinal plant species used by the Dayak Kenyah community in Punan Gong Solok Village, North Kalimantan, and to describe their utilization patterns based on local ethnomedicinal practices. A qualitative descriptive method was employed, involving interviews, participatory observations, and plant identification. Data were collected using snowball sampling for informants and purposive sampling for plant exploration. The results revealed 46 species from 25 families used in traditional medicine, dominated by the Zingiberaceae and Araceae families. Leaves were the most commonly used plant part (33.3%), followed by tubers, roots, and stems. The plants were used to treat stomachaches, gastritis, kidney stones, external wounds, and respiratory disorders, with preparation methods including boiling, pounding, and infusion. These findings highlight the importance of preserving local knowledge as a basis for developing phytopharmaceuticals and promoting community-based conservation.